Bioinformatics methods for high-throughput DNA sequencing data - xiaojuan Zhan; dengju Yao; huaiqiu Zhu (大数据)
DNA sequence data generated by high-throughput sequencing technology is short in length, and the amount of data is enormous. The challenges and opportunities of the big data in high-throughput sequencing environment were analyzed. The data compression, the assembly of metagenomic sequence data, and algorithms and tools of metagenomic sequence data analysis also were summarized and discussed. Finally, the future of the study on short read DNA sequence data in high-throughput sequencing environment was discussed.